Subtypes of optic ataxia: reframing the disconnection account. - Buxbaum LJ; Coslett HB (Neurocase (Taylor & Francis Ltd), 1997)
Optic ataxia (OA) is a disorder of visually guided reaching which is usually attributed to a disconnection of visual information from motor systems. The traditional disconnection account, however, cannot explain the most common form of the disorder, in which misreaching occurs only when targets are presented in non-foveal vision and not when they are viewed directly. On the basis of data from two subjects, as well as recent physiological evidence, we offer a new account which can accommodate the 'non-foveal' subtype of OA. We suggest that the fundamental deficit in OA is a failure to transform spatio-motor information into frames of reference appropriate to the reaching apparatus, that is, to code locations and actions within shoulder-, arm-, and hand-centered coordinate systems. We suggest that in the absence of normal spatio-motor transcoding, the accurate foveal reaching of some patients with OA may be accomplished by a pathologic linkage of systems mediating spatio-motor transformations for the eye and hand. This linkage permits patients with 'non-foveal' OA to reach accurately to locations at which they gaze, but not elsewhere.